2016
DOI: 10.1007/s40858-016-0102-8
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Meloidogyne incognita, Meloidogyne javanica and Pratylenchus brachyurus in sunflower cultivars adapted to the tropical region of Brazil

Abstract: The continuous soybean-maize crop succession in the tropical region of Brazil has led to significant increases in the population size of root-knot (Meloidogyne incognita and M. javanica) and root-lesion nematodes (Pratylenchus brachyurus), which make soils unsuitable for soybean cropping. A greenhouse study was conducted to identify sunflower genotypes adapted to the tropical region of Brazil and that are resistant to M. incognita, M. javanica and/or P. brachyurus. Two experiments for each nematode were conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 7 publications
1
6
0
1
Order By: Relevance
“…The introgression of the PI 595099 soybean genotype with a high level of resistance to M. incognita was developed by the Georgia Agricultural Experiment Station (EUA), while BRS 133, by contrast, is a susceptible genotype developed by the National Soybean Research Center—Embrapa Soybean (Brazil). Both genotypes are agriculturally important and have been used in soybean breeding programs and in studies to identify genetic resistance to parasitic nematodes [ 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. Recently, an increasing number of studies exploring the mechanisms underlying the resistance and susceptibility of diverse crops to M. incognita have been performed using omic approaches [ 51 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ].…”
Section: Introductionmentioning
confidence: 99%
“…The introgression of the PI 595099 soybean genotype with a high level of resistance to M. incognita was developed by the Georgia Agricultural Experiment Station (EUA), while BRS 133, by contrast, is a susceptible genotype developed by the National Soybean Research Center—Embrapa Soybean (Brazil). Both genotypes are agriculturally important and have been used in soybean breeding programs and in studies to identify genetic resistance to parasitic nematodes [ 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. Recently, an increasing number of studies exploring the mechanisms underlying the resistance and susceptibility of diverse crops to M. incognita have been performed using omic approaches [ 51 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the same authors found four resistant cultivars of sunflower to M. paranaensis , another important plant-parasitic nematode of coffee plants. As for P. brachyurus , Dias et al . (2016) identified several sunflower genotypes resistant to this species but not to M. incognita .…”
Section: Resultsmentioning
confidence: 99%
“…As soybean is a photoperiod-sensitive and self-pollinated species, days to flowering and maturity, duration of flowering-to-maturity and plant height are crucial for soybean adaptability and yield (Zhang et al, 2015). In Central Brazil, early soybean varieties allow farmers to grow a second crop either of corn or cotton in the summer, to optimize the use of machinery and the available workforce, resulting in increased profit for the farmer (Dias et al, 2016). This practice reduces risks of yield losses due to pests and environmental stresses by keeping soybean on the field for a shorter period, which minimizes crop exposure to insect and disease.…”
Section: Susceptible Genotypes To the Soybean Mosaicmentioning
confidence: 99%